2017
DOI: 10.3389/fphys.2017.00805
|View full text |Cite
|
Sign up to set email alerts
|

Intravesicular Phosphatase PHOSPHO1 Function in Enamel Mineralization and Prism Formation

Abstract: The transport of mineral ions from the enamel organ-associated blood vessels to the developing enamel crystals involves complex cargo packaging and carriage mechanisms across several cell layers, including the ameloblast layer and the stratum intermedium. Previous studies have established PHOSPHO1 as a matrix vesicle membrane-associated phosphatase that interacts with matrix vesicles molecules phosphoethanolamine and phosphocholine to initiate apatite crystal formation inside of matrix vesicles in bone. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…While the Ca 2+ transport mechanism in these cells is relatively well understood ( Lacruz, 2017 ; Lacruz et al, 2017 ; Varga et al, 2018 ), much less is known about the mechanism of phosphate transport into the enamel matrix. Some possibilities include transport into the cells of the enamel via Na + -phosphate cotransporters of the SLC20 and SLC34 gene families ( Merametdjian et al, 2018 ; Beck, 2019 ) followed by secretion across the apical membrane or into matrix vesicles ( Pandya et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the Ca 2+ transport mechanism in these cells is relatively well understood ( Lacruz, 2017 ; Lacruz et al, 2017 ; Varga et al, 2018 ), much less is known about the mechanism of phosphate transport into the enamel matrix. Some possibilities include transport into the cells of the enamel via Na + -phosphate cotransporters of the SLC20 and SLC34 gene families ( Merametdjian et al, 2018 ; Beck, 2019 ) followed by secretion across the apical membrane or into matrix vesicles ( Pandya et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the samples were in 100% light cure technovit (Technovit 7200, EXAKT), the next step was to polymerize and embed the samples. Next, the samples were sectioned using a diamond bandsaw (EXAKT 300 CP), ground and polished to achieve 50–70 µm thin sections as described in our previous study [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…In enamel, Phospho1 -/mice exhibited a 25% increase in tissue volume, with a significantly reduced level of mineralization. (47) The authors furthermore reported that ablation of PHOSPHO1 caused loss of enamel prism morphology and an impaired crystal organization compared to wild-type mice.…”
Section: Dental Mineralizationmentioning
confidence: 99%